EFEKTIVITAS MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR MATEMATIKA SEKOLAH DASAR - Agung Sapto Nugroho; Nyoto Harjono (Universitas Borneo Tarakan, 2020)
Abstract: The purpose of this research was to re-analyze the use of cooperative learning typeÂ numbered head together model in increasing the learning outcome in mathematics studies subject. The research method was meta-analysis. The research began with formulating research problems, then trancing relevant research result to be analyzed. The data was collected by browsing article, electronic journals, and essay using â€œlearning outcomesâ€, â€œnumbered head together modelâ€, and â€œMathematics Studies of Primary Educationâ€. The searching result showed that there were 13 articles, electronic journals, and essay but only 9 relevant articles, electronic journals, and essay. The data were analyzed using qualitative descriptive analysis. The analysis result showed that cooperative learning type numbered head togetherÂ model could improve studentâ€™s learning from the lowest 15,81%. to the highest 91,88% and the mean was 43,85%.Abstrak: Tujuan dari penelitian ini adalah untuk menganalisis kembali penggunaan model pembelajaran tipe kooperatif tipeÂ numbered head together dalam menaikkan hasil belajar pada mata pelajaran Matematika. Metode penelitian adalah meta-analisis. Penelitian dimulai dengan merumuskan masalah penelitian, kemudian menguji hasil penelitian yang relevan untuk dianalisis. Data dikumpulkan dengan menelusuri artikel, jurnal elektronik, dan esai menggunakan